2004
DOI: 10.1002/aic.10124
|View full text |Cite
|
Sign up to set email alerts
|

Why liquid displacement methods are sometimes wrong in estimating the pore‐size distribution

Abstract: The liquid displacement method is a commonly used method to determine the pore size distribution of micro-and ultrafiltration

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…The characteristic parameter used to discuss the effect of the flowing continuous phase is the wall shear stress. Previous studies have shown that the droplet size decreases as the wall shear stress increases [5,7,19]. One popular explanation of this phenomenon is that the flowing continuous phase creates the drag force that pulls the droplets away from the pore mouths after reaching a certain size [15].…”
Section: Shear Induced Droplet Formation According To the Force Balanmentioning
confidence: 98%
See 1 more Smart Citation
“…The characteristic parameter used to discuss the effect of the flowing continuous phase is the wall shear stress. Previous studies have shown that the droplet size decreases as the wall shear stress increases [5,7,19]. One popular explanation of this phenomenon is that the flowing continuous phase creates the drag force that pulls the droplets away from the pore mouths after reaching a certain size [15].…”
Section: Shear Induced Droplet Formation According To the Force Balanmentioning
confidence: 98%
“…For extensive and recent reviews on membrane emulsification consult Joscelyne and Trägårdh [4], Charcosset et al [5] and Gijsbertsen-Abrahamse et al [7]. Other authors have described droplet formation depending by considering the type of mechanisms causing the droplets to detach and or the systems sensitivity to operating conditions [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, for droplets between 10-100 µm microchannel (MC) emulsification process has, in particular, been considered an effective method of producing uniform particles, with typical coefficients of variation of 5% (this compares with normal CVs of about 10% for other membranes). The current state of membrane emulsification technology and the underlying process phenomena have been reviewed by several authors [93][94][95][96]. These articles are mainly focused on the influence of process parameters and membrane properties on the droplet size distribution and the transmembrane flux.…”
Section: Particle Manufacturementioning
confidence: 99%
“…Here we study droplet formation in a cross-flow membrane emulsification (XME) geometry, a high-throughput method for generating monodisperse droplets [8][9][10]. In XME, the dispersed phase (DP) is forced through an orifice in a planar membrane into a simple shear flow set up by a second continuous phase (CP) flowing parallel to the membrane surface; see Fig.…”
mentioning
confidence: 99%